If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 6y) + 4(2x + -9y) = 0 (3x * 5 + 6y * 5) + 4(2x + -9y) = 0 (15x + 30y) + 4(2x + -9y) = 0 15x + 30y + (2x * 4 + -9y * 4) = 0 15x + 30y + (8x + -36y) = 0 Reorder the terms: 15x + 8x + 30y + -36y = 0 Combine like terms: 15x + 8x = 23x 23x + 30y + -36y = 0 Combine like terms: 30y + -36y = -6y 23x + -6y = 0 Solving 23x + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 23x + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 23x + 0 = 0 + 6y 23x = 0 + 6y Remove the zero: 23x = 6y Divide each side by '23'. x = 0.2608695652y Simplifying x = 0.2608695652y
| 28-7x-4=(-7x-7) | | -180=2x+7(5x-2) | | 9(3y+2)=7(4y+7) | | 2/3x-1/2=6 | | -7+2=16 | | 5a+3=-42 | | 18/432 | | Sin(a)=.345 | | 7x(3x^2)+4=0 | | 2p+5r=p | | 70p+30q= | | 5a+3=42 | | -6x-120=-180 | | 4(3x-2)+6=-7(3-2x)+5 | | 5x+1+3x+3=20 | | 5x/9=1/2 | | 1x-4=-1+2x | | 1/2x=21/10 | | -2m+15=-67 | | 2(x+5)=-4(x-7) | | -4+3x^2-4x=0 | | (x/500)/y | | 3m+48=65 | | -y-57=-40 | | 5y-2=9y+10 | | (5-2x)(-X)+x^2= | | 5x+2=3x-12 | | 3/4=z=12 | | 48-6a=64 | | (17y-4)+(7x+30)=180 | | 24a+72b-40= | | 27-3m=45 |